The Effectiveness of Gargling Decoction of Green Betel Leaf (Piper Betle L) and Guava Leaf (Psidium Guajava) Against Plaque Index - Vega Roosa Fione; Jeane d'Arc Zavera Adam; Ni Made Ayu Sri Lestari (Eduvest - Journal of Universal Studies, 2024)
The purpose of this study was to determine the effectiveness of gargling using a decoction of green betel leaves (Piper betle Linn) and decoction of guava leaves (Psidium Guajava) against plaque index. Method: This is the true experiment method with a two-group pre and post test design. This research was carried out in the last week of March to the second week of April 2023 at the Department of Dental Health, Poltekkes, Ministry of Health, Manado.The data obtained were then tabulated and analyzed using paired sample t-test. This research instrument uses diagnostic tools and PHP plaque index examination format. Results: The results showed that the average value of plaque index in the group that received gargling treatment using green betel leaf decoction was 3.38 before gargling and 1.33 after gargling. This value has a decreasing difference of 2.05. Furthermore, the average value of plaque index in the group that received gargling treatment using guava leaf decoction was 3.39 before gargling and 2.41 after gargling. This value has a decreasing difference of 0.98. The paired test results of the t-test sample obtained a value of p-value = 0.000. This value indicates that the treatment given provides effective in reducing plaque index. Conclusion: It can be concluded that the gargling a decoction of green betel leaves and guava leaves can reduce the plaque index where the decoction of green betel leaves is more effective in reducing the plaque index.